Efficacy of Diode Laser for the Management of Potentially Malignant Disorders - kundoor, Vinay Kumar Reddy; Patimeedi, Ashwini; Roohi, Shameena; Maloth, Kotya Naik; Kesidi, Sunitha; Masabattula, Geetha Kumari (Journal of Lasers in Medical Sciences, 2015)
Introduction: Laser dentistry is a one of the upcoming advanced treatment modality for oral mucosal lesions. Diode laser is a soft tissue laser that has found much acceptance in all branches of dentistry. Available compact size and feasibility has render diode laser an enhanced tool for today’s clinical practice. The aim of this study is to determine the efficacy and safety of diode laser for the management of white lesions such as oral leukoplakia (OL) and oral lichen planus (OLP). Methods: The study was conducted by using diode laser 980 nm on 10 patients with white lesions (5 OL and 5 OLP) aged between 35 to 65 years. Results: Of the 10 patients (5 OL and 5 OLP), 3 patients (30%) complained of moderate pain and 7 patients (70%) complained of mild pain, for first 3 days after laser irradiation, and pain disappeared at end of first week. There was no recurrence of the lesion during the 6-month follow up. Conclusion: Diode lasers provide acceptable clinical improvement of potentially malignant lesions with minimal side effects. It can be considered one of the best alternative treatment modality for oral mucosal lesions.